2016
DOI: 10.1136/archdischild-2015-310313
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of infants born at 22–27 weeks' gestation in Victoria according to outborn/inborn birth status

Abstract: Mortality rates remained higher for outborn livebirths at 22-27 weeks' gestation compared with inborn peers in 2010-2011. Outborn infants admitted to NICU did not have substantially different rates of mortality or serious morbidity compared with inborns, with the exception of cPVL. Longer-term health consequences of outborn birth before 28 weeks' gestation need to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 36 publications
8
55
0
Order By: Relevance
“…26,27 More locally, survival following NICU admissions in WA (44/78 or 56% at 23 weeks and 112/139 or 81% at 24 weeks) is higher than reported survival from NSW and ACT (11/41 or 27% at 23 weeks and 110/186 or 59% at 24 weeks) over a similar time period, 2007-2011, 13 and is similar to reported survival from NICU admissions in Victoria from 2010 to 2011 (11/16 or 69% at 23 weeks and 41/71 or 58% at 24 weeks). 14 The major findings from this study provide a challenge to commonly held beliefs about survival and long-term outcomes of children born at the limits of viability, before 25 weeks of gestation. The majority of children born alive and admitted to NICU for care survived without moderate or severe disability (78%).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…26,27 More locally, survival following NICU admissions in WA (44/78 or 56% at 23 weeks and 112/139 or 81% at 24 weeks) is higher than reported survival from NSW and ACT (11/41 or 27% at 23 weeks and 110/186 or 59% at 24 weeks) over a similar time period, 2007-2011, 13 and is similar to reported survival from NICU admissions in Victoria from 2010 to 2011 (11/16 or 69% at 23 weeks and 41/71 or 58% at 24 weeks). 14 The major findings from this study provide a challenge to commonly held beliefs about survival and long-term outcomes of children born at the limits of viability, before 25 weeks of gestation. The majority of children born alive and admitted to NICU for care survived without moderate or severe disability (78%).…”
Section: Discussionmentioning
confidence: 82%
“…Published Australian studies of neonatal intensive care unit (NICU) admissions have reported survival of 11 of 41 (27%) infants at 23 weeks and 110 of 186 (59%) infants at 24 weeks in New South Wales and the Australian Capital Territory 13 and survival of 11 of 16 (69%) infants at 23 weeks and 41 of 71 (58%) infants at 24 weeks in Victoria. 14 Interpretation of survival and long-term outcomes are also complicated by use of varying population denominators, such as individual NICU admissions, regional NICU admissions, hospital births or regional births. 15 Studies vary in the assessment of developmental impairments, differences in measurement, age of measurement, use of corrected versus chronological age, use of normative comparison groups and differences in classification and differentiation of neurosensory impairments.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Hypothermia is a common morbidity associated with birth before arrival, irrespective of gestational age or birth weight . We have previously reported an 11‐fold increase in mortality in extremely preterm BBAs transferred to a tertiary centre by ambulance paramedics and admitted to a neonatal intensive care unit (NICU) in Victoria . The current study identified that a significant proportion of BBAs died before they could be admitted to a nursery, and a high proportion of those who survived to nursery admission died within six hours of birth.…”
Section: Discussionmentioning
confidence: 99%
“…During the past 5 years, large cohort studies from developed nations in North America, 1113,20,21 South America, 22 Europe, 14,15,2325 Asia, 18,19,26 and Australia 27 have reported estimates of gestational age-specific survival following periviable birth. Direct comparisons of estimated survival rates among these studies are limited, however, by potential biases introduced from differences in the data sources, ascertainment of death, selection of denominators, and definitions of live birth.…”
Section: Estimates Of Gestational-age Specific Survivalmentioning
confidence: 99%